Draʿ Abu el-Naga, Ägypten: Untersuchungen zu Formation und Entwicklung einer oberägyptischen Residenznekropole - Polz, Daniel (e-Forschungsberichte des DAI, 2023)
The past two spring seasons in the field were dedicated to the continuation of archaeological work in Area H of the Institute’s project in Draʿ Abu el-Naga in the north-eastern part of the Theban Necropolis, opposite the modern city of Luxor / Upper Egypt. Area H is located in the middle of the foothills of Draʿ Abu el-Naga and contains two widely visible landmarks: the remains of the mud-brick pyramid of king Nub-Kheper-Ra Intef (late 17th dynasty, ca. 1580 BC), and the large 12-pillared ‘Saff’ tomb no. 232 (TT 232, early 18th dynasty, ca. 1550 BC). Over centuries, both monuments and installations in their environment seem to have served as platforms, even local centers, not only of funerary but also religious and cultic activities.